Tumor markers: myths and facts unfolded. - Faria, S. C.; Sagebiel, T.; Patnana, M.; Cox, V.; Viswanathan, C.; Lall, C.; Qayyum, A.; Bhosale, P. R. (Abdominal Radiology, 2019)
Objective: The purpose of this article is to review the most commonly used tumor markers in abdominal and pelvic tumors, describe their limitations and explain how to use them in the context of known cancer in order to optimize multidisciplinary care of oncologic patients. Conclusion: Tumor markers are important for the diagnosis, staging, monitoring of treatment and detection of recurrence in many cancers. This knowledge is crucial in the daily interpretation of images of oncologic and non-oncologic patients. However, radiologists should also be aware of the limitations of the most commonly used tumor markers and they should not be used solely, but interpreted in conjunction with diagnostic imaging, clinical history and physical examination that will help optimize the multidisciplinary care and management of oncologic patients.